Política e sociedade nas estradas transversais da América Latina : o neoliberalismo e o posiberalismo? (1980-2014) - Dos Santos Sousa, Andreza; Sessa, Leandro; Morais de Medeiros Neta, Olivia (2015)
Understanding the problems of social movements in Latin America, the work of the left or center-left, the emergence of multilateral organizations, and their influence in Latin American countries are important to understand a little more about the current historical, economic and social context, as well as the policies were designed in these countries. It is a complex scenario, marked by strong changes, where the facts occur simultaneously. Neoliberalism arises in order to reduce the role of the state, but this accentuates social inequalities, raises unemployment rates, increases the criminalization of social protest, and dictates what each country should specialize in the name of a so-called structural reform . The social struggles were intense and the left comes to power, but undergoes changes in some countries takes a center-left stance, but that is not everything, because the multilateral organizations despite giving in to the pressures of social movements, within the scope of social policies they still interfere with other policies as we can verify in the case of Brazil with the Basic Education Program for the North and Central West Regions (Monhangara Program), which was one of the projects financed by the World Bank. These are some elements that are present at the crossroads of Latin America living a post-liberal policy.
Compreender a problemática dos movimentos sociais na América Latina, a atuação da esquerda ou centro-esquerda, o surgimentos de organizações multilaterais, suas influências nos países latinoamericanos são importantes para entendermos um pouco mais sobre o atual contexto histórico, econômico e social, bem como as políticas sociais foram concebidas nesses países. É um cenário complexo, marcado por mudanças fortes, onde os fatos ocorrem de forma simultânea. Surge o neoliberalismo com o intuito de reduzir o papel do Estado, mas isso acentua as desigualdades sociais, eleva das taxas de desemprego, aumenta a criminalização dos protestos sociais, além de ditar o que cada país deve se especializar em nome de uma chamada reforma estrutural. As lutas sociais foram intensas e a esquerda chega ao poder, mas sofre mudanças em alguns países assume uma postura centro-esquerda, mas isso não é tudo, pois as organizações multilaterais apesar de ceder às pressões dos movimentos sociais, no âmbito das políticas sociais elas ainda interferem nas demais políticas como podemos verificar no caso do Brasil com o Programa de Educação Básica para as Regiões Norte e Centro-Oeste (Programa Monhangara) que foi um dos projetos financiados pelo Banco Mundial. Esses são alguns elementos que estão presentes nas encruzilhadas da América Latina vivendo uma política pós-liberal.
Keywords: Latin America; Social movements; Government of the left; Multilateral organizations; América Latina; Movimento sociais; Governo de esquerda; Organizações multilaterais^lpt